2012
DOI: 10.1371/journal.pone.0049834
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Clinical and Immunological Markers for Predicting Virological Failure in a HIV/AIDS Treatment Cohort in Busia, Kenya

Abstract: BackgroundIn resource-limited settings where viral load (VL) monitoring is scarce or unavailable, clinicians must use immunological and clinical criteria to define HIV virological treatment failure. This study examined the performance of World Health Organization (WHO) clinical and immunological failure criteria in predicting virological failure in HIV patients receiving antiretroviral therapy (ART).MethodsIn a HIV/AIDS program in Busia District Hospital, Kenya, a retrospective, cross-sectional cohort analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
26
5
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 14 publications
5
26
5
2
Order By: Relevance
“…South Africa has used VL testing preferentially for monitoring of ART since program inception, which, is now also strongly recommended by the World Health Organisation (WHO) [2]. There are currently over 3900 National Department of Health (NDoH) clinics providing ART initiation and monitoring services in South Africa [3].…”
Section: Introductionmentioning
confidence: 99%
“…South Africa has used VL testing preferentially for monitoring of ART since program inception, which, is now also strongly recommended by the World Health Organisation (WHO) [2]. There are currently over 3900 National Department of Health (NDoH) clinics providing ART initiation and monitoring services in South Africa [3].…”
Section: Introductionmentioning
confidence: 99%
“…Our work also shed light on the age difference of male and female acquiring infection and provided evidence that in fact female are more prone to HIV infection than male at younger age. The HAART enrolled patients had significantly lower viral copy number in their serum compared to that of naïve but was not consistent with the relapsed number of CD4 count which may provide the case of immunological failure [13]. This study elicits the need of more study related to immunological parameters thus providing precise diagnosis and surveillance of HIV patients.…”
Section: Discussionmentioning
confidence: 85%
“…Serum albumin, which is not routinely measured in developing countries and is not available in most of the laboratory at ART center which is the most common laboratory parameter for nutritional assessment with low serum albumin indicating malnutrition [5,6,9,10,12]. Lipid profile abnormalities have been reported in the early stages of HIV infection and become more evident with the disease's progression [13,14]. There is large number of cytokines increase and serum triglyceride, HDL-cholesterol decrease during HIV infection [15].…”
Section: Introductionmentioning
confidence: 99%
“…(8) also found that immunological and clinical failure had poor prediction of virological failure. The study showed the sensitivity of immunological and clinical failure to detect viral failure was 36.4%, specificity was 83.5% and the positive-predictive value was 12.3%.…”
Section: Discussionmentioning
confidence: 96%